Methylammonium bismuth bromide perovskite single crystal growth and its application as saturable absorber for mode-locked fiber laser - Mansor, M.; Zainol Abidin, N.H.; Liew, J.Y.C.; Md Zain, A.R.; Alresheedi, M.T.; Ng, E.K.; Mahdi, M.A. (Elsevier, 2025)
This study investigates the morphology, structure and optical properties of methylammonium bismuth bromide, MA3Bi2Br9 (MBB) perovskite single crystals grown via slow evaporation method with different molar ratios of methylammonium bromide to bismuth bromide (3:1, 3:2, 3:3 and 3:4). Comparative analysis of the crystals produced under the different molar ratios revealed distinct differences in crystal morphology. The structural characterization confirmed the perovskite phase formation and exhibited favorable optical properties for saturable absorption. The MBB saturable absorber demonstrated a modulation depth of 9.75% and when employed in an erbium-doped fiber laser, it was able to generate mode-locked pulses with an average duration of 942.8 fs. The generated pulses were stable even when operated at high humidity for long periods. These results showcase the potential of MBB perovskite crystals as effective saturable absorbers for ultrashort pulses generation in fiber lasers and for other potential optoelectronic applications.